Using the Art Museum as a Bridge to the Future - Šola, Tomislav (2004)
The museum's tasks: fulfilling the great expectations of the society as the answer to decisions taken by the society, start a discussion about the role of the museums in the society to map our possibilities and necessities, to reform the system and to keep it active at the same time.